The difference in intervention of sexual abuse prevention by two variance professions on primary school children in Padang - Neherta, Meri; Machmud, Rizanda; Damayanti, Rita; Afrizal, . (Indian Journal of Community Health, 2017)
Background: The number of primary school children that become victims of sexual abuse are always increasing year by year. Aims & Objectives: This study evaluated the effectiveness of interventions for sexual abuse prevention on knowledge and assertiveness behaviour of primary school age children, which were committed by two different professions, namely nurses and teachers. Material & Methods: The study method was a quantitative with quasi-experimental design types of non-equivalent control group design. The population in this study were all primary school children in the city of Padang, consist of 91,966 children, with total sample of 1,112 children. Measurement of the knowledge and behaviour of children was performed 4 times total, then followed by statistical tests with GLM Repeated Measures. Results: Mean and standard deviation values from knowledge of nurses intervention group: p1(3,37; +1,37), p2(4,62; +1,72), p3(4,97; +1,53), p4(5,52; +1,20). Mean and standard deviation value from the group’s assertiveness: s1(24,44; +4,20), s2(28,66; +2,58), s3(31,38; +1,50), s4(32,80; +2,115) with p value =0,00. While the Mean and standard deviation values from knowledge of teacher’s intervention group: p1(3,21; +1,30), p2 (3,83; +1,14), p3(4,01; +0,99), p4(4,53; +0,875). Mean and standard deviation value from the group’s assertiveness: s1(24,47; +4,38), s2(27,56; +3,65), s3(27,34; +4,40), s4(29,90; +2,87) with p value =0,00. Scores difference between the nurses intervention group with teachers intervention group is 0.73 points for knowledge and 2.00 points for assertiveness behaviour. Conclusion: Intervention model that conducted by nurses is the best model. It is recommended that this model can be used as a model for primary prevention of sexual abuse against primary school age children.